IREC2015 the Sixth International Renewable Energy Congress 2015
DOI: 10.1109/irec.2015.7110944
|View full text |Cite
|
Sign up to set email alerts
|

Matlab/Simulink model of photovoltaic modules/strings under uneven distribution of irradiance and temperature

Abstract: Quite often PV modules operate in mismatch conditions, that are caused by: technology, design, installation and operative conditions. As far as the operative conditions are concerned, shading mainly causes uneven distribution of irradiance on PV cells, in turn shading creates not uniform distribution of temperature on the PV modules. There are also situation where the uneven distribution of temperature is a design input such as in the solar hybrid photovoltaic/thermal (PV/T) system. In this context a Matlab/Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The equivalent circuit of a PV cell is shown in Fig ( 4). It includes a current source, a diode, a series resistance and a shunt resistance [3,28].…”
Section: A Pv Arraymentioning
confidence: 99%
“…The equivalent circuit of a PV cell is shown in Fig ( 4). It includes a current source, a diode, a series resistance and a shunt resistance [3,28].…”
Section: A Pv Arraymentioning
confidence: 99%
“…In [5][6][7], MATLAB-Simulink is used to establish a simulation model of photovoltaic array under the shadowing condition and concluded that the output of the PV array exhibits a multipeak and stepped shape under the shadow condition. In [8], it is concluded that hot spots occur when the short-circuit current of the photovoltaic cells is smaller than the electric current flowing through the cells based on the simulations and experimental studies of the reverse Bishop model of photovoltaic arrays.…”
Section: Introductionmentioning
confidence: 99%
“…1. Mathematical Model of the photovoltaic ModuleThe PV simple equivalent circuit contains the next basic components; current source, series resistor, diode and shunt resistor as displayed in Fig.2 [4,5]…”
mentioning
confidence: 99%